2003
DOI: 10.1073/pnas.0337743100
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of core helices and rapid tertiary folding of a small bacterial group I ribozyme

Abstract: Compact but non-native intermediates have been implicated in the hierarchical folding of several large RNAs, but there is little information on their structure. In this article, ribonuclease and hydroxyl radical cleavage protection assays showed that base pairing of core helices stabilize a compact state of a small group I ribozyme from Azoarcus pre-tRNA ile . Base pairing of the ribozyme core requires 10-fold less Mg 2؉ than stable tertiary interactions, indicating that assembly of helices in the catalytic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
166
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(183 citation statements)
references
References 54 publications
16
166
1
Order By: Relevance
“…In 20 mM MgCl 2 , 10% of the pre-tRNA folded in the deadtime of the assay (, 30 s), and the remainder reached the native state at a rate of 0.47 min 21 ( Figure 4A). Thus, the average folding time of the pre-tRNA is much longer than that of the ribozyme, 9 consistent with the presence of metastable intermediates.…”
Section: Mg 21 -Dependence Of Folding Kineticsmentioning
confidence: 55%
See 3 more Smart Citations
“…In 20 mM MgCl 2 , 10% of the pre-tRNA folded in the deadtime of the assay (, 30 s), and the remainder reached the native state at a rate of 0.47 min 21 ( Figure 4A). Thus, the average folding time of the pre-tRNA is much longer than that of the ribozyme, 9 consistent with the presence of metastable intermediates.…”
Section: Mg 21 -Dependence Of Folding Kineticsmentioning
confidence: 55%
“…We have found that the Azoarcus L-9 ribozyme folds in 50 -100 ms in a concerted fashion. 9 Here, we find that correct folding of the pre-tRNA is delayed by non-native base-pairs between the tRNA and the intron. Thus, the exons contribute to splice site recognition, but increase the probability of misfolding in vitro.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…44 Solvent accessibility of the IRES was probed using Fe(II)-EDTA and H 2 O 2 in a solution of RNA renatured in the presence or absence of IRAB (20 mM) followed by primer extension analysis with fluorescently labeled primers, resolved by capillary electrophoresis. The results yielded cleavage information at single nucleotide resolution, reporting on solvent exposure of the IRES nucleotides (Fig.…”
Section: Irab Induces a Local Structural Reorganization Of The Ires Ementioning
confidence: 99%